1996
DOI: 10.1097/00000542-199612000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Midazolam and Remifentanil during Monitored Anesthesia Care

Abstract: Use of remifentanil alone for MAC did not provide optimal sedation during local anesthesia. However, 0.05 to 0.1 microgram.kg-1.min-1 remifentanil in combination with 2 mg midazolam given intravenously, provided effective sedation and analgesia during MAC in healthy patients classified as American Society of Anesthesiologists status 1 to 2. Midazolam also produced dose-dependent potentiation of remifentanil's depressant effect on respiratory rate. In outpatients receiving a combination of midazolam and remifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 12 publications
4
56
2
10
Order By: Relevance
“…Aynı görüşü destekleyen benzer çalışmalar mevcuttur. (3,5,12,13) Son yıllarda yayınlanan çalışmalarda, MAB'da farklı dozlarda uygulanan deksmedetomidin infüzyonunun, lokal veya rejyonal anestezi ile yapılan girişimlerde yeterli analjezi ve sedasyon sağladığı gös-terilmiştir. (6,7,14) Çalışmamızda, M/R grubunda, D grubuna göre istatistiksel olarak anlamlı düzeyde hızlı sedasyon sağlandı.…”
Section: Discussionunclassified
“…Aynı görüşü destekleyen benzer çalışmalar mevcuttur. (3,5,12,13) Son yıllarda yayınlanan çalışmalarda, MAB'da farklı dozlarda uygulanan deksmedetomidin infüzyonunun, lokal veya rejyonal anestezi ile yapılan girişimlerde yeterli analjezi ve sedasyon sağladığı gös-terilmiştir. (6,7,14) Çalışmamızda, M/R grubunda, D grubuna göre istatistiksel olarak anlamlı düzeyde hızlı sedasyon sağlandı.…”
Section: Discussionunclassified
“…Use of higher doses of midazolam to reduce recall can potentiate the respiratory depressant effects of remifentanil. 34 More recently, remifentanil has been used in combination with propofol in an attempt to reduce recall and minimize respiratory complications. [14][15][16] Moerman et al investigated the combination of TCI propofol with either TCI remifentanil or a manual infusion of remifentanil in 60 patients undergoing sedation for colonoscopy.…”
Section: Remifentanilmentioning
confidence: 99%
“…Regarding sedation and analgesia, other studies have demonstrated that the association of remifentanil (bolus of 0.5 µg.kg -1 .min -1 over 30 seconds, followed by continuous intravenous infusion, 0.05 µg.min -1 ) and midazolam (2 mg IV) is effective, since 66% of the patients did not experience pain or discomfort during the procedures, and provided light sedation. Besides, few side effects were observed (16% of nausea and 2% of vomiting) 37,38 . Therefore, remifentanil would be the ideal analgesic component in sedations and analgesia for percutaneous intracardiac electrophysiological studies, ablation of arrhythmias with radiofrequency catheter, or both, if it were not for the results of our study.…”
Section: Discussionmentioning
confidence: 92%
“…Atualmente, acredita-se que a diminuição da pressão arterial média causada pelo remifentanil seja devida à vasodilatação periférica e conseqüente diminuição da resistência vascular sistêmica, por mecanismo endotélio-dependente, relacionado com a liberação de prostaciclina e óxido nítrico 33 . Shinohara e col. demonstraram que em ratos com neuroeixo intacto (com a resposta do reflexo barorreceptor manti- 37,38 . Portanto, não fossem os resultados desse estudo, o remifentanil seria o componente analgésico ideal nas sedações e analgesia para a realização de estudo eletrofisiológico intracardíaco percutâneo, ablação de disritmias por cateter de radiofreqüência, ou ambos.…”
Section: Discussionunclassified
See 1 more Smart Citation